[The lives of Mang Pandoy, Eden, and Vilma Santos [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Probe tells the changes in the lives of four Filipinos for whom 1992 was of some significance; Mang Pandoy, who is President Ramos symbol of the Filipino thirsting for economic upliftment; Victor, the streetkid Probe discovered four years ago; Emy, the bargirl left jobless and heartbroken with the closing of the U.S. bases; and Vilma Santos, the star for all seasons who is now Congressman Mrs. Ralph Recto.
Mang Pandoy (14 min.) -- Victor (11 min.) -- Eden (17 min.) -- Vilma Santos (15 min.) -- Epilogue (3 min.)
VHS.
Keywords: Poverty -- Philippines; Filipinos -- Economic conditions; Poor -- Philippines; Street children -- Philippines; Philippines -- Economic conditions -- 1992.